2019
DOI: 10.1177/1179558119871269
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and Consequences of Disordered Sleep in PCOS

Abstract: Polycystic ovary syndrome (PCOS) is a common hormonal disorder that is characterized by hyperandrogenism and menstrual irregularity. Affected women have a high prevalence of insulin resistance and related metabolic complications. The frequency of sleep disturbances appears to be increased in women with PCOS, although most studies so far have included more severely affected obese women with PCOS who are referred to tertiary care clinics and may not represent the general population of women with PCOS. This artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…This is why sleep disorders in patients with PCOS are twice as common as in ordinary people [ 80 ]. Hyperandrogenism, IR, and low estrogen and progesterone levels with PCOS have all been suggested to cause OSA in PCOS patients [ 81 ]. IR is associated with irregular sleep breathing [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is why sleep disorders in patients with PCOS are twice as common as in ordinary people [ 80 ]. Hyperandrogenism, IR, and low estrogen and progesterone levels with PCOS have all been suggested to cause OSA in PCOS patients [ 81 ]. IR is associated with irregular sleep breathing [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other reported risk factors for decreased sleep quality during the COVID-19 pandemic are changes to sleep patterns ( 62 ), worries about health ( 68 ), financial consequences ( 69 ), social interactions ( 70 ), reduced physical activity ( 63 ), and gender with women being reportedly 56% more likely than men to experience sleep disruption during this pandemic ( 71 ). As such, it is plausible that such factors further contribute to a potential multifactorial effect upon an already “at risk” population ( 72 ), which clearly exacerbates sleep disruption and may result in reduced QoL. Indeed, the results of the present study support this notion, since women with PCOS who reported negative sleep effects during the COVID-19 pandemic also exhibited reduced QoL (as measured by the PCOSQOL) compared to those without any, or with positive effects on sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Since insulin resistance is an important etiological feature of PCOS, affected women are at higher risk of developing type 2 diabetes and related metabolic complications [ 38 ]. On the other hand, it has been reported that sleep disturbances are common in PCOS, and some form of them, like obstructive sleep apnoea, in turn, exacerbates insulin resistance [ 39 ]. In accordance with our results, there were studies that have shown treatment with exogenous melatonin had favorable effects on sleep quality, which was assessed by the PSQI, especially in the adults with metabolic disorders [ 40 ].…”
Section: Discussionmentioning
confidence: 99%